Design of Temperature Control System of HFO Fuel Type on Ship Based PLC - Eddy Setyo Koenhardono; Juniarko Prananda; M Arif Fachruddin (Institut Teknologi Sepuluh Nopember, 2018)
Fuel is one of the important component of ship operations. The overall operating cost of the vessel, approximately 60% consists of fuel costs. The unavailability of fuel causes the ship's operational processes to be adversely affect the company from both technical and material terms. It is a bad condition if ship’s fuel does fulfilled the time schedule. To reach the fuel operation criteria and help ships crew operate the fule system, we propose the method to control fuel system. Our objection is how to make ship fuel system can be operated automatically as well as temperature control system on the vessel using PLC. This automation system relies on high level sensors and low level sensors as well as temperature sensors in each tank to trigger the performance of each of the fuel system support equipment such as pumps, valves, heaters. The sensor and thermometer in the tank will be processed by the PLC prior to controlling the equipment. Processing is sequentially adjusted to the processing sequence of HFO fuel. Processing is done based on existing ship data but still using the control manually. As well as recommendations from the classification bureau and machine manufacturers. The work process of the system can be monitored as a whole through Human Machine Interface. The monitor consists of a view that contains all the work of the existing system. The PLC used is OMRON CPM2A with CX-Programmer software and CX-Designer monitor. So by simply using a control device in the form of PLC, HFO processing can be operated automatically both when the ship is idle or in sail condition